2018
DOI: 10.3390/genes9070334
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Promoters of Genes in Lipid Metabolism and Their Transcriptional Response to STAT3 under Leptin Signals

Abstract: We characterized the promoters of target genes of the signal transducer and activator of transcription 3, STAT3 (carnitine palmitoyltransferase I, CPT Iα1b, acetyl-CoA carboxylase alpha, ACCα; fatty acid synthase, FAS; and peroxisome proliferator-activated receptor gamma, PPARγ) in a teleost Pelteobagrus fulvidraco. Binding sites of STAT3 were predicted on these promoters, indicating that STAT3 probably mediated their transcriptional activities. Leptin had no effect on the activity of ACCα and PPARγ promoters,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…However, as far as we know, fish leptin is hardly available commercially at present. Therefore, recombinant human leptin has widely been used to investigate the function of fish leptin [ 22 , 23 , 37 , 38 ]. Thus, in the present study, recombinant human leptin was used to study promoters function of sf-1 and cyp17α in yellow catfish.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as far as we know, fish leptin is hardly available commercially at present. Therefore, recombinant human leptin has widely been used to investigate the function of fish leptin [ 22 , 23 , 37 , 38 ]. Thus, in the present study, recombinant human leptin was used to study promoters function of sf-1 and cyp17α in yellow catfish.…”
Section: Discussionmentioning
confidence: 99%
“…For example, several studies reported that leptin attenuated gonadotropin or growth factor-stimulated steroidogenesis in isolated theca and granulosa cells [ 17 , 18 ], but other studies pointed out that leptin induced the synthesis of estrogen in ovary and ovarian follicles [ 19 , 20 ]. Signal transducer and activator of transcription 3 (STAT3) is identified as the most important factor to transduce the leptin signal [ 21 , 22 , 23 ]. In mammals, studies have suggested that leptin modulated steroidogenic by STAT3 [ 13 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The hiTAIL-PCR (high-efficiency thermal asymmetric interlaced PCR) method [ 28 ] was used to clone the promoter sequences, and the protocols followed our previous studies [ 29 , 30 ]. The specific primers were listed in the Supplementary Table S1 .…”
Section: Methodsmentioning
confidence: 99%
“…Plasmid transfections and activity assays of luciferase followed our recent publications [ 29 , 30 ]. Briefly, HepG2 cells were cultured in DMEM medium (10% FBS) in an incubator with 5% CO 2 at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…For promoter luciferase assays, HepG2 cells were counted and seeded at a density of 1 × 10 5 in twenty-four well plates, then cultured and transfected as mentioned in our recent studies (19,23) . Briefly, to study the nSREBP-1-induced changes in promoter activities, we co-transfected 300 ng of nSREBP-1 plasmid or the same amount of pcDNA3.1(þ) plasmid (300 ng, control) with 500 ng of each of these luciferase reporter plasmids of srebp-1, accα, scd1 and fas promoters into HepG2 cells using Lipofectamine 2000 (Invitrogen) at 80-90 % confluence, respectively.…”
Section: Luciferase Assay Of Srebp-1 Accα Scd1 and Fas Promotersmentioning
confidence: 99%